Evolution of Electronic Root Canal Length Measurement Device -A Literature Review - Shivangi Shekhar; P.Laxmish Mallya (Institute of Medico-legal Publications Pvt Ltd, 2021)
Summary: An electronic apex locator(EAL) is a device used to measure the working length (WL) of theroot canal space(RCS) and proved to be a great help to the endodontist reducing radiation exposure ofboth patients and clinicians and providing accurate reading for the WL. Evolution of different generationsof EAL helped to eradicate the shortcomings of the previous generations providing precise measurementof the WL. Electronic Apex locators are used to detect any perforations, furcation involvement, also usedto detect horizontal fractures, also to detect internal or external resorption. With so many uses, it is stillcontraindicated in patients with pace makers and inaccurate reading in canals with common irrigants likeEthylenediamine tetraacetic acid and sodium hypochlorite. It requires dry or partially dry canals to givereadings with accuracy. It also gives inaccurate reading in the presence of semi-conductive materials andhence the canals should be free of them. Though it provides almost precise measurement of the WL it cannotbe replaced with radiographs but can be used as an adjunct with it. Pre- and post-operative radiographs arestill necessary for the success of the endodontic treatment as it provides an idea for any periapical lesionand degree of curvature of roots. Acceptance of an electronic apex locator to determine the correct WLhas still not gained approval worldwide. Lack of exposure to the technology by the operator, inadequateknowledge of the root canal anatomy and cost of the instrument are also the factors for it not gainingworldwide acceptance.